2020
DOI: 10.1177/0194599820974685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on Presentation of Sudden Sensorineural Hearing Loss at a Single Institution

Abstract: The coronavirus disease 2019 (COVID-19) pandemic resulted in widespread unprecedented changes to the health care system. Herein, we sought to assess the impact of the viral outbreak on clinical presentations of sudden sensorineural hearing loss (SSNHL) at a single academic center. Our results demonstrate a decrease in the absolute number of patients presenting with SSNHL to our institution during the initial onset of the COVID-19 pandemic compared to an analogous time frame 1 year prior. However, the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 7 publications
4
29
0
2
Order By: Relevance
“…Data about the impact of COVID-19 on audiological emergencies such as SSNHL are currently inconsistent and controversial. Chari et al [4] reported a decrease in the absolute number of patients who presented with SSNHL during the COVID-19 lockdown period (March to May 2020) in comparison to the similar time frame 1 year before (13 versus 71 patients). However, the ratio of diagnosis over the total patients evaluated was not very different between the two periods (1.91% vs 1.77%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Data about the impact of COVID-19 on audiological emergencies such as SSNHL are currently inconsistent and controversial. Chari et al [4] reported a decrease in the absolute number of patients who presented with SSNHL during the COVID-19 lockdown period (March to May 2020) in comparison to the similar time frame 1 year before (13 versus 71 patients). However, the ratio of diagnosis over the total patients evaluated was not very different between the two periods (1.91% vs 1.77%).…”
Section: Discussionmentioning
confidence: 95%
“…A large decrease in the number of Ear Nose and Throat outpatient urgent consultations was observed during the first phase of the pandemic probably due to national lockdown orders associated with patients' reticence and fear of going to the hospitals [2] . Consequently, a reduction in the diagnosis of many otorhinolaryngological and audiological disorders such as epistaxis, pharyngo-tonsillitis, otitis media, equilibrium disorders, and sudden sensorineural hearing loss (SSNHL) has been reported [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In their comments on the study by Kılıç et al, Luca et al stated that no serious increases in case numbers were reported in the pandemic period regarding hearing loss, the result in the study by Kılıç et al could be coincidental, and it needed to be investigated [ 21 ]. Chari et al found the incidence of SSNHL similar between March and May in the pandemic period and the same months in the previous year and stated that the COVID-19 virus does not lead to an increase in the incidence of SSNHL [ 22 ]. In a study conducted by Mustafa, while no significant difference could be determined between asymptomatic COVID-19 patients and healthy individuals in terms of their pure tone audiometry results at low frequencies, worse results were reported in the COVID-19 patients at high frequencies and in transient evoked otoacoustic emissions (TEOAE), and it was argued that COVID-19 and the cochlea could be associated [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…). None of these 13 patients diagnosed with SSNHL were found to be positive for COVID-19 [28]. It should be noted that SSNHL is probably multifactorial and whether COVID-19 has an effect on these factors is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…During the COVID-19 pandemic, from March 15, 2020, to May 31, 2020, there were 13 diagnosed SSNHL cases out of 681 suspected cases (1.91%). None of these 13 patients diagnosed with SSNHL were found to be positive for COVID-19 [ 28 ]. It should be noted that SSNHL is probably multifactorial and whether COVID-19 has an effect on these factors is unknown.…”
Section: Reviewmentioning
confidence: 99%